If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2p + -15p = 17 Combine like terms: -2p + -15p = -17p -17p = 17 Solving -17p = 17 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '-17'. p = -1 Simplifying p = -1
| 16y^3=25x | | 2/5(45) | | 9/r=3 | | 2/5x-3/43 | | 11x=17x-30 | | (3+7i)+(4-3i)= | | 6r+9= | | -35+5= | | 5s+2s=7 | | 2A=41-A | | 2(r-3)=8 | | 2(e-3)=8 | | 3n+7=9n+21 | | 5.5+(-6.9)= | | 6y(3yx+5X)+2w=1 | | x/6=-22/33 | | 2+5xi-3y=14xi+3x-5yi | | 4(u-3)+8(2u-3)=4 | | 5m-4m=45 | | 2x+86=172 | | -12h+2h=-20 | | (z+43)+z+z=180 | | 6=3a-8 | | 4(4-7x)=-180 | | (z+43)+2z=180 | | 5(9+2x)=125 | | f(-2)=2x+1 | | f(2)=3x-5 | | 5y-11=4y-3 | | -46+-59= | | 7x^2+13x-20=0 | | 5+3x-x=5 |